Manufacture and Sensor’s Characterization for Optimizing the Manufacture of Resistance Sensors Based on Tea with Natural Sugar and Artificial Sugar - S, Cindy Septiani; Defanny; Rakhmadi, Frida Agung (Proceeding International Conference on Science and Engineering, 2020)
This research aims to identify sensors. This research was carried out through 3 stages, namely: designing resistance sensors, making resistance sensors, testing resistance sensors. The sensor sheceme by using software Fritzing. The tools used in making these sensors include Power and solder, for materials used are plain PCB, 2.2K? resistors, copper wire, paper, pens, rulers, and materials for testing are tea, natural sugar and artificial sugar. Sensor testing is performed in data collection by measuring voltage. Because the data generated is in the form of voltage. By doing 2 variations of the volume of 50ml and 100ml which is done 5 times with each volume repetition. The data obtained is then processed by calculating the mean and its uncertainty. The results of this research provide information that the natural sugar tea voltage for 50ml volume (0.958 ± 0.1916) 80% repeatability. And for 100ml volume (0.884 ± 0.1768) the compatibility is 80%. While the artificial sugar tea voltage for 50ml volume (1.488 ± 0.2976) 80% compatibility and for 100ml volume (1.484 ± 0.2968) 80% repeability. From the data obtained, both can be seen to have different voltage values and the same compatibility value, which is 80%. Because the resulting repeatability does not reach national standards, this sensor cannot be used.